Kajian Feminisme Poskolonial pada Tokoh Firdaus dalam Novel Perempuan di Titik Nol - Zahra'ni, Izzahtu Nuha; Albar, Dini Salima; Susanto, Dwi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to analyze the forms of oppression experienced by Firdaus in the novel Woman at Point Zero through the lens of Gayatri C. Spivak’s postcolonial feminist approach. The novel represents the experiences of women living in an oppressive patriarchal and feudal society. Firdaus, the main character, is confronted with various harsh realities as a woman who lacks power, voice, and control over her own body. This study uses a qualitative approach with descriptive methods, aiming to understand social phenomena related to women’s experiences. Data collection was conducted using the reading and note-taking method, which involved analyzing the novel's text and recording relevant quotations. The data source used is the Indonesian translation of Woman at Point Zero (Perempuan di Titik Nol) by Nawal El Saadawi, translated by Amir Sutaarga in 2002. The data consists of narratives describing characters, dialogues, and events that illustrate the forms of oppression experienced by Firdaus. These forms of oppression include physical and sexual violence, economic inequality, and the silencing of her voice. In the face of such marginalization, Firdaus resists in various ways—by remaining silent, rejecting imposed norms, reclaiming control over her body, and ultimately taking the extreme step of killing her pimp. The death sentence she receives is not an act of despair, but a final form of resistance over her body and the choices she makes as a subaltern woman